2022
DOI: 10.1021/acsanm.2c03035
|View full text |Cite
|
Sign up to set email alerts
|

Dry and Binder-Free Deposition of Single-Walled Carbon Nanotubes on Fabrics for Thermal Regulation and Electromagnetic Interference Shielding

Abstract: Conductive textiles with good flexibility and durability are highly demanded for wearable electronics. However, the common approaches of making conductive textiles require multi-step solvent processes, which is tedious and environment unfriendly. Herein, the high-quality single-walled carbon nanotubes (SWCNTs), synthesized by the floating catalyst chemical vapor deposition method, were directed and dry coated on the melt-blown fabrics (MBFs) recycled from the waste masks with binder-free chemical. The obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The EMI shielding property of a material strongly depends on its electrical conductivity. , As shown in Figure a, pure GNP film exhibited the highest average EMI SE T of 46.6 dB because of its best electrical conductivity. The average EMI SE T of the 10%BC, 20%BC, 30%BC, 40%BC, and 50%BC was 43.0, 36.4, 30.0, 23.6, and 18.3 dB, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The EMI shielding property of a material strongly depends on its electrical conductivity. , As shown in Figure a, pure GNP film exhibited the highest average EMI SE T of 46.6 dB because of its best electrical conductivity. The average EMI SE T of the 10%BC, 20%BC, 30%BC, 40%BC, and 50%BC was 43.0, 36.4, 30.0, 23.6, and 18.3 dB, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Recently [100], conductive and flexible melt-blown fabrics were coated with SWCNTs by chemical vapor deposition, where the melt-blown fabrics were recycled from face masks. The results showed that the sheet resistance of the conductive fabrics depended on the deposition time and was 245, 116, and 57 Ω/ for deposition times of 1 h, 2 h, and 3 h, respectively.…”
Section: Conductive Fabrics Based On Swcntsmentioning
confidence: 99%
“…Therefore, in intelligent electronic devices with high strain capacity, mechanical stability, wave insulation and thermal tunability, modied conductive acrylic resin elastomers are the best choice currently. Since the shielding performance of composite materials mainly depends on the high aspect ratio, low density, etc., of the conductive ller, 23,38 the one-dimensional tubular structure of carbon nanotubes (CNTs) has become a popular choice, due to its ultrahigh tensile strength, high conductivity, and thermal conductivity, [39][40][41][42][43] as an ideal material for preparing exible stretchable electromagnetic shielding lms with heat collection function. This work combines single-walled carbon nanotubes (SWCNTs) with acrylic resin-based elastomers by spraying to obtain an electromagnetic shielding lm with high toughness and stretchability, which can be effectively controlled through applied areal strain variables.…”
Section: Introductionmentioning
confidence: 99%